Histological Changes of Hepatic Coli-Granulomas in Rooster (Gallus domesticus) Infected with Escherichia coli - Mohammed A. Ali; Firas A. Alhasson; Thaer R. Mhahal; Shireen J. Khaleel; Samerah A. Daaj (Kufa Journal for Veterinary Medical Sciences)
A granulomatous reaction including the accumulation and aggregation of macrophage cells, either alone or in conjunction with epithelial cells, that may combine to produce multinucleated (giant) cells characterizes the chronic inflammatory condition known as hepatic granuloma. Normally, these granulomas have fibrous fibers and lymphocytes encircling them. Hepatic granuloma is linked to coli bacillosis caused by Escherichia coli, which can spread to various internal organs and result in a systemic lethal disease. In a particular study, the author observed that hepatic granulomas were surrounded by lymphocytes and a zone of macrophage cells. Additionally, fibrosis in the portal area was attributed to E. coli infections. Grossly affected livers were found to contain multiple, firm, pale-yellow, spherical masses with numerous nodules. Furthermore, the study revealed the presence of granulomas in at least one or more than one organs, most commonly in the ceca, and often  in an organ like the liver. The study also noted that the necrotic lesion was distinguishable from the surrounding areas of heterophils and giant cells in early  stages of granulomas.